2005
DOI: 10.1093/chemse/bji014
|View full text |Cite
|
Sign up to set email alerts
|

Metallic Taste from Electrical and Chemical Stimulation

Abstract: A series of three experiments investigated the nature of metallic taste reports after stimulation with solutions of metal salts and after stimulation with metals and electric currents. To stimulate with electricity, a device was fabricated consisting of a small battery affixed to a plastic handle with the anode side exposed for placement on the tongue or oral tissues. Intensity of taste from metals and batteries was dependent upon the voltage and was more robust in areas dense in fungiform papillae. Metallic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 27 publications
(34 reference statements)
3
80
0
Order By: Relevance
“…The results in the present study complement, from a materials science perspective, the 292 work by Lawless et al (2005) by comparing other solid metals (silver, tin, chromium and 293 gold, some of which are used in modern cutlery) to those known to produce metallic tastes 294 directly in the oral cavity (e.g. zinc and copper).…”
Section: Discussion 277 278supporting
confidence: 52%
“…The results in the present study complement, from a materials science perspective, the 292 work by Lawless et al (2005) by comparing other solid metals (silver, tin, chromium and 293 gold, some of which are used in modern cutlery) to those known to produce metallic tastes 294 directly in the oral cavity (e.g. zinc and copper).…”
Section: Discussion 277 278supporting
confidence: 52%
“…These events included three reports of metallic taste, one report of a tingling sensation in the mouth, and one report of tongue sensitivity. The metallic taste can be explained by the finding that electrical stimulation can induce metallic sensations [37]. All these adverse events were considered to be mild in severity [19].…”
Section: Development Of the Brainport Artificial Vision Devicementioning
confidence: 99%
“…If this value exceeds the upper -α critical to the Neweel and Macfarlane (1987) table, we can conclude that significant differences exist among the samples. The data showed that the sample cooked formed (Gonzalez et al, 1998;Shiffmann, 2000;Zacarias et al, 2001;Lawless et al, 2005;Hoehl et al, 2010). The results of the study by Hoel et al (2010) indicate that there is a difference in the identification of basic tastes and metallic sensations, and corresponding thresholds depending on the water in which substances are diluted.…”
Section: Selection and Training Evaluation Of The Capability To Discrmentioning
confidence: 99%
“…Therefore, investigators should direct attention to water quality, especially when analysis of metallic sensation is important. Deionized or distilled water has been suggested because it ensures constant composition (Lawless et al, 2005). However, the pH of the deionized water is below neutral and therefore generates a bitter taste or metallic sensation (Whelton et al, 2007).…”
Section: Selection and Training Evaluation Of The Capability To Discrmentioning
confidence: 99%